Phylogenetic and functional mechanisms of direct and indirect interactions among alien and native plants. (25th April 2016) - Feng, Yanhao; van Kleunen, Mark
Summary: Disentangling direct and indirect interactions among alien and native plants is essential to understanding the success of alien plants in multispecies communities, but studies have only focused on direct pairwise interactions. Moreover, it is also essential to explore phylogenetic and functional mechanisms driving these interactions. In a greenhouse experiment, we selected nine groups of alien and native plant species from the herbaceous flora of Germany to disentangle their direct and indirect interactions. Each group had an alien (A) that is common or rare in Germany (i.e. non‐native range), two natives that are phylogenetically closely related (Nclose ) and distantly related (Ndist ) to A respectively, and a distantly related "target" native (T). We grew the four species of each group alone, and in two‐species and three‐species combinations. Specifically, we tested whether competition is greater between A and Nclose than between A and Ndist, whether presence of Nclose rather than Ndist indirectly alleviates competition of A on T, and whether these interaction patterns depend on commonness of A. Moreover, we tested how intensity of these interactions is explained by phylogenetic distance, functional traits (height, seed mass, SLA, leaf size, specific root length, leaf area ratio, root length ratio (root length/plant mass), shoot weight ratio) and traits‐based functional distance. We found A had stronger competition on Nclose than on Ndist . In turn, A was more suppressed by Nclose than by Ndist, but this was only true for rare rather than common A. The presence of Ndist rather than Nclose indirectly reduced competition of A on T. The intensity of these interactions was not explained by phylogenetic or functional distance, but by some of the functional traits. Specifically, a plant experienced stronger competition when it was shorter and had smaller leaves and lower shoot weight ratio, and when its neighbours were taller, had greater SLA, leaf area ratio and shoot weight ratio, and had a lower root length ratio. Synthesis . Functional traits can help explain competitive interactions. While direct competition tended to be stronger between more closely related alien and native plants, this did not indirectly facilitate other co‐occurring native plants. Abstract : It is essential to disentangle direct and indirect interactions among alien and native plants, and to explore niche‐based phylogenetic and functional mechanisms driving these interactions. We showed that while direct competition tended to be stronger between more closely related alien and native plants, this did not indirectly facilitate other co‐occurring native plants. Moreover, functional traits helped explain these interactions.